Local Communities’ Perceptions about the Impacts of Water Hyacinth Infestation in Lake Victoria on Economic Activities in Nyalenda B Ward, Kisumu County, Kenya - Mbaka, John (East African Journal of Environment and Natural Resources, 2023)
Water hyacinth (Eichhornia crassipes) is ranked as one of the most invasive weeds causing negative effects on aquatic ecosystems around the world. In the last decades, there has been increased interest in the impacts of water hyacinth and how it can be utilised in various applications such as animal feeds and fertiliser production, wastewater treatment, biofuel production and as raw material for handicraft products.
Keywords: Lake; Weed; Invasive; Natural Resource; Local Community